2021
DOI: 10.3390/app11209643
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Annatto Tocotrienol and Palm Tocotrienol-Rich Fraction on Chondrocytes Exposed to Monosodium Iodoacetate

Abstract: Background: This study aimed to compare the chondroprotective efficacy and mechanism of annatto tocotrienol (AnTT) and palm tocotrienol-rich fraction (PT3) using SW1353 chondrocytes treated with monosodium iodoacetate (MIA). Methods: The chondrocytes were incubated with AnTT or PT3 in advance or concurrently with MIA for 24 h. The viability of the cells was tested with an MTT assay. The 8-isoprostane F2-α, extracellular matrix proteins, metalloproteinase and sex-determining region Y box protein 9 (SOX9) levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Among the OA studies, one involved oral supplementation of palm tocotrienol (400 mg/kg/day for 6 months) among patients with OA (Kellgren–Lawrence score of 2 and 3) [ 46 ]; two studies involved oral supplementation of palm (100 mg/kg/day for 4 weeks) or annatto tocotrienol (50–150 mg/kg/day for 4 weeks) in rats with monosodium iodoacetate-induced OA [ 47 , 48 ]; another study used SW1353 chondrosarcoma cells exposed to monosodium iodoacetate and palm (25–50 µg/mL for 24 h) or annatto tocotrienol (10–20 µg/mL for 24 h) in the experiment [ 49 ]. Glucosamine sulphate was used as the positive control in the in vivo studies [ 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the OA studies, one involved oral supplementation of palm tocotrienol (400 mg/kg/day for 6 months) among patients with OA (Kellgren–Lawrence score of 2 and 3) [ 46 ]; two studies involved oral supplementation of palm (100 mg/kg/day for 4 weeks) or annatto tocotrienol (50–150 mg/kg/day for 4 weeks) in rats with monosodium iodoacetate-induced OA [ 47 , 48 ]; another study used SW1353 chondrosarcoma cells exposed to monosodium iodoacetate and palm (25–50 µg/mL for 24 h) or annatto tocotrienol (10–20 µg/mL for 24 h) in the experiment [ 49 ]. Glucosamine sulphate was used as the positive control in the in vivo studies [ 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro study demonstrated that tocotrienol, especially the annatto derivative, could elicit the cellular protective mechanism of SW1353 chondrocytes against damage by monosodium iodoacetate. This was evidenced by an increased collagen II type α1 to collagen I type α1 ratio, and increased SRY-box transcription factor 9 and aggrecan expression in chondrocytes exposed to both monosodium iodoacetate and annatto tocotrienol [ 49 ]. These markers indicated the differentiation and functionality of chondrocytes [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytotoxicity of tocotrienols was determined using the yellow tetrazolium salt 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) according to previous studies with slight modification [ 6 ]. Briefly, 100 µL of human chondrosarcoma SW1353 cells with a density of 5 × 10 4 cells/mL were seeded in a 96-well plate with complete media for 24 h. On the next day, the media were removed and replaced with 100 µL of complete media with a series of concentrations of tocotrienol (10–50 µM) for another 24 h. At the end of the treatment, 20 µL of MTT solution (5 mg/mL) was added to each well and then further incubated for another 4 h inside a 37 °C incubator.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, rice bran oil contains lesser vitamin E (around 300 mg/kg) with around 25% tocopherols, 17% tocotrienols and a negligible amount of γ-tocotrienol (γ-T3) [ 5 ]. Vitamin E extracted from annatto beans is unique in composition with the absence of tocopherol but 10–16% γ-T3 and 84–90% of δ-tocotrienol (δ-T3) [ 6 , 7 ]. Plant oil-derived tocotrienol or tocotrienol-rich fraction (TRF) is a more viable candidate for commercialization than their pure isomers which require complicated and expensive isolation procedures [ 5 ].…”
Section: Introductionmentioning
confidence: 99%